2022
DOI: 10.1007/s10237-022-01567-4
|View full text |Cite
|
Sign up to set email alerts
|

A new membrane formulation for modelling the flow of stomatocyte, discocyte, and echinocyte red blood cells

Abstract: In this work, a numerical model that enables simulation of the deformation and flow behaviour of differently aged Red Blood Cells (RBCs) is developed. Such cells change shape and decrease in deformability as they age, thus impacting their ability to pass through the narrow capillaries in the body. While the body filters unviable cells from the blood naturally, cell aging poses key challenges for blood stored for transfusions. Therefore, understanding the influence RBC morphology and deformability have on their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 79 publications
(122 reference statements)
0
4
0
Order By: Relevance
“…1 ), fully matches those reported for the RBC damage during storage (Putter and Seghatchian, 2017 ). The only difference is that electroporation induces these morphological changes within few seconds, whereas the RBC storage lesions progress much more slowly over several weeks (Putter and Seghatchian, 2017 ; Geekiyanage et al, 2020 ; Karandeniya et al, 2022 ). The following sections analyze the mechanism of the self-propelled RBC motion using image-based cell tracking and cell velocimetry.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 ), fully matches those reported for the RBC damage during storage (Putter and Seghatchian, 2017 ). The only difference is that electroporation induces these morphological changes within few seconds, whereas the RBC storage lesions progress much more slowly over several weeks (Putter and Seghatchian, 2017 ; Geekiyanage et al, 2020 ; Karandeniya et al, 2022 ). The following sections analyze the mechanism of the self-propelled RBC motion using image-based cell tracking and cell velocimetry.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanisms of hemolysis and related mechanical properties of erythrocytes have been the subject of numerous experimental and theoretical studies (Zhang and Brown, 2008 ; Klöppel and Wall, 2011 ; Boal, 2012 ; Faghih and Sharp, 2019 ; Wu et al, 2019 ; Craven et al, 2019 ; Asaro and Zhu, 2020 ; Horobin et al, 2020 ; Karandeniya et al, 2022 ). A recent study identified hemolysis as a key event in the clearance and turnover of billions of senescent erythrocytes per day in the spleen (Klei et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…− Tear cells (dacryocytes) are drop-shaped or pear-shaped erythrocytes with one large spicule with a blunt end. Cell size varies [9,10].…”
Section: Erythrocyte Morphology Studymentioning
confidence: 99%
“…The changes which revealed the alteration of RBC morphology are detected later after the first 24 hours of induction of sepsis [ 14 , 15 ]. Finally, the presence of disintegrated erythrocytes and also RBC aggregates were observed [ 16 ].…”
Section: Introductionmentioning
confidence: 99%